The Penalty of Mobility in Manila during Periods of Public Health Crises - Pante, Michael D. (2020)
Mobility seems to impose a paradoxical penalty on individuals based in Metro Manila. Looking at the experiences of public health crises during the American colonial period and the present-day Covid-19 pandemic, this essay focuses on the inordinate restrictions on and blame assigned to the least mobile segments of the population despite the fact that such crises are aided by heightened mobility. Past and present disease outbreaks force us to acknowledge that our cities contain groups of people with varying levels of mobility, another form of social inequality that badly needs to be addressed.
Keywords: COVID-19 pandemic; Public health; Transportation; Cities and towns; Urbanization; Social mobility; Informal settler families (ISF)